Greetings!
To solve this, you can multiply one of the equations by a number so that one of the unknown values are the same as the other equation. Or simply multiply both numbers before the x together:
(-2x + 5y = -15 ) x 5 =
-10x + 25y = -75
(5x+2y=-6) x -2 =
-10x -4y = 12
Now, you can add or minus the two equations, but seeing as both values before the x are negative we can add the two equations to cancel out the x:
-10x -4y = 12 +
-10x + 25y = -75 =
0x + 21y = -63
21y = -63
Simply divide -63 by 21 to find y:
-63 ÷ 21 = -3 , so the value of y = -3
Now you can substitute this value into one of the equations:
5x + 2y = -6
5x + 2(-3) = -6
5x = -6 - (-6)
5x = -6 + 6
5x = 0
x = 0
So that means x = 0 and y = -3
Hope this helps!